A Formal Framework for Crisis Management Describing Information Flows and Functional Structure. (2016) - Bénaben, Frédérick
Abstract: Crisis management is a very empirical activity, most of the time based on human ability to deal with the unexpected and to fusion all kinds of information to provide the best decision and the best associated action. However, the information flows and the high level activities are not so well described. This article aims at providing a formal framework describing these elements. The presented framework is the basement for the establishment of a software suit dedicated to formally manage information flows in crisis context and exploit them to provide crisis managers with a computerized decision support system. Even if this software system is not the topic of the paper, it is the justification for the presented structuring framework. The framework is based on two main structuring elements: the nature of available or required information and the functions that should be able to use them to provide crisis management domain with a relevant decision support system.